Magnetic resonance imaging and single photon emission tomography in treatment-responsive and treatment-resistant schizophrenia. - Lawrie, S; Ingle, G; Santosh, C; Rogers, A; Rimmington, J; Naidu, K; Best, J; O'Carroll, R; Goodwin, G; Ebmeier, K (1995)
BACKGROUND: Patients with schizophrenia differ from controls in several measures of brain structure and function, but it is uncertain how these relate to clinical features of the illness. We dichotomised patient groups by treatment response to test the hypothesis that treatment-resistant patients exhibit more marked biological abnormalities than treatment-responsive patients. METHOD: Twenty treatment-responsive and 20 treatment-resistant patients with schizophrenia, matched for sex, age, and illness duration, were compared by magnetic resonance imaging, single photon emission tomography, and detailed neuropsychological assessment. RESULTS: Brain-imaging variables were not statistically related to treatment response, although poorly responsive patients had lower volumes of most brain structures. Several highly significant differences emerged between patient groups on neuropsychological testing. Episodic memory functioning distinguished patient groups even after we controlled for global cognitive impairment. CONCLUSIONS: Cerebral structure and blood flow have a limited effect on treatment response in schizophrenia, but long-term episodic memory impairment is associated with, and may predict, poor prognosis.